Vitamin D ameliorates adipose browning in chronic kidney disease cachexia - Wai W. Cheung; Wei Ding; Hal M. Hoffman; Zhen Wang; Sheng Hao; Ronghao Zheng; Alex Gonzalez; Jian-Ying Zhan; Ping Zhou; Shiping Li; Mary C. Esparza; Richard L. Lieber; et al. (Scientific Reports, 2020)
Abstract Patients with chronic kidney disease (CKD) are often 25(OH)D3 and 1,25(OH)2D3 insufficient. We studied whether vitamin D repletion could correct aberrant adipose tissue and muscle metabolism in a mouse model of CKD-associated cachexia. Intraperitoneal administration of 25(OH)D3 and 1,25(OH)2D3 (75 μg/kg/day and 60 ng/kg/day respectively for 6 weeks) normalized serum concentrations of 25(OH)D3 and 1,25(OH)2D3 in CKD mice. Vitamin D repletion stimulated appetite, normalized weight gain, and improved fat and lean mass content in CKD mice. Vitamin D supplementation attenuated expression of key molecules involved in adipose tissue browning and ameliorated expression of thermogenic genes in adipose tissue and skeletal muscle in CKD mice. Furthermore, repletion of vitamin D improved skeletal muscle fiber size and in vivo muscle function, normalized muscle collagen content and attenuated muscle fat infiltration as well as pathogenetic molecular pathways related to muscle mass regulation in CKD mice. RNAseq analysis was performed on the gastrocnemius muscle. Ingenuity Pathway Analysis revealed that the top 12 differentially expressed genes in CKD were correlated with impaired muscle and neuron regeneration, enhanced muscle thermogenesis and fibrosis. Importantly, vitamin D repletion normalized the expression of those 12 genes in CKD mice. Vitamin D repletion may be an effective therapeutic strategy for adipose tissue browning and muscle wasting in CKD patients.